Kajian Penggerusan (Scouring) pada Dinding Saluran Air Waringin Jaya Kecamatan Bojonggede Kabupaten Bogor - Chika Restu Maulidina, Chika; Hariati, Feril; Nandiasa, Jantiara Eka; Taqwa, Fadhila Muhammad Libasut (Tameh, 2024)
The Waringin Jaya river is a tributary of the Ciliwung river that passes through Waringin Jaya village. Although it is not classified as a river with a large discharge, it is capable of eroding riverbanks and retaining walls, endangering the community. This study aims to analyze the magnitude and depth of local scour that occurs on gabion-type retaining walls, located in the Waringin Jaya River basin, Kec. Bojonggede, Kab. Bogor using the Hec-Ras computer application. The calculation of the discharge plan for the return period of 2 years, 5 years, 10 years, 20 years, 25 years, 50 years, and 100 years using the rational method was carried out based on daily rainfall data at the Citeko Meterological Station and the West Java Climatology Station with a data length of 2007 - 2021. Based on the calculations that have been carried out, the water level on the retaining wall with a flood return period of 2 years, 5 years, 10 years, 20 years, 25 years, 50 years, and 100 years is 0.92 m; 0.99 m; 1.03 m; 1.04 m respectively; 1.06 m; 1.08 m; and 1.10 m, while based on the analysis conducted with Hec-Ras bridge scour, the scour that occurs at each return period flood discharge is 1.24 m; 1.32 m; 1.35 m; 1.39 m; 1.40 m; 1.44 m; and 1.46 m, respectively.